Comprometimento organizacional dos servidores técnicos administrativos da Universidade Federal de Mato Grosso - Silva, Emerson José da (2019)
The labor field settings are under transformation, demanding from woker a state of constant Adaptation to the new Technologies and distinet work relationships. The public service and its servers, perceive the effects of these changes as necessary to provide eficiente servisse to citzens. Physical and psychological well-being of public servants must be assured along the performance of their tasks, converging personal and organizational objectives. This is a descriptive, explorative research of quantitative nature, which has used as a measurement tool of these componentes Organizational Commitment Basis Scale (EBACO), a tool which was developed to assess the of organizational commitment considering contexts and realities of Brazilian organizations. The research could count on 318 public servants, which correspond to 20% of active workes of the institution. The analysis of the results indicated that the servants that the servants are positively commited to the UFMT regardin identification with the filosofhy and organizational objectives as well as to good organizational performance. The interpretation of the results with a low score indicate that servants do not have consolidated emotional bonds with the UFMT, and do not fell belonging to a group, nor a member of the institution, which may affect the relationships with the work place and people in the organization. The studied servants, at the same time crave for a solid career and seek to build it by himself, with no emotional bonds. This research amplifies the studies on QLW and organizational commitment at public service, contributing for the comprehension and recognition of the importance of position held by the servant in the Federal Públic Higher Education institutions. Knowing the profile of organizational commitment of the public servente at UFMT is importante to the development of practices and policies of people’s management which align with the well-being of servants and better eficiency and effectiveness in public services, besides coolaborating with the expansion of this topic in diferente Brazilian public organizational contexts. As a reflexion, it is importante to reinforce that the recognition and appreciation of the servants by their own coworkersand by the organization, might influence in the personal and professional development, reverberating in the construction of the professional identify of this worker.